Impacts of deforestation for agriculture on soil physical characteristics in the steeplands - Jusoff, Kamaruzaman; Nik Ab. Majid, Nik Muhamad (1987)
The impacts of deforestation for agriculture on steepland soil physical properties at Sungai Tekam Forest Reserve, Pahang were investigated by collecting 100 7.6 cm diameter soil core samples to a depth of cm in plots established randomly in cleared and forested areas. Deforestation significantly decreases soil moisture content, total pore space, saturated hydraulic conductivity and available water-holding capacity (AWC). It increases bulk density, soil temperature and resistance to root penetration. The increase could be attributable mainly to the disturbance of the surface soil, destruction of its structure causing severe soil compaction by the present deforestation method of using heavy crawler tractors. These detrimental effects of deforestation on soil physical properties can be minimized through skillful manipulation of logging machines and sound soil management and conservation measures taken at the right time.